New insights of winter canola survival, seed quality, and yield for the Great Plains region and the United States - Secchi, Mario Ariel (Kansas State University, 2022)
Canola (Brassica napus L.), also known as rapeseed, is an emerging valuable crop with edible oil quality. Climate models forecast erratic temperature and rainfall patterns with contrasting impacts on canola production. The main projected annual changes are linked to increased frequency of extreme heat and drought events during the summer months, challenging the overall production of row crops. The adoption of winter oilseed crops such as winter canola could be a feasible option to overcome these challenges and to diversify agricultural systems. This dissertation is organized in four chapters which explore in detail the main challenges and potential expansion of winter canola production. Chapter 1 provides an overall introduction and context in production for this crop. Chapters 2 and 3 summarize a series of multi-environment studies with more than 25 states and 200 genotypes (during the 2003-2018 period) providing critical information for breeding programs, agronomy management, and the future direction of canola production. Chapter 4 compiles information from a total of 37 papers gathering 1794 observations to execute a meta-analysis on the effect of heat and drought on the formation of seed yield and quality on canola crop. Chapter 5 presents the impact of future weather changes (focused on temperature and precipitation) on seed yield via the utilization of crop growth models to provide an assessment on potential yield shifts across the US. In summary, this dissertation provides critical information identifying potential environments suitable for winter canola production. New insights ranging from improving our understanding of winter canola survival, geographical variation for yield and oil productivity, impacts of critical stressors such as heat and drought on seed yield and quality traits, and lastly, future weather impact on seed yield across the US is assessed to evaluate geographical changes in production and to develop potential mitigation strategies.
Keywords: Rapeseed; Diversification; Expansion; Challenges; Future